Abandoned housing projects in Malaysia and the prospect of DP: an overview - Abdul Razak, Dzuljastri; Mohammed, Mustafa Omar; Tarique, Kazi Md. (ELSEVIER, 2015)
Owning a house is a dream that every individual cherishes. In Malaysia, both the banking sector and the government have expended relentless efforts to ensure Malaysians have access to financing and affordable houses. These efforts are however being derailed by alarming cases of abandoned housing projects (AHPs) that have affected a substantial number of house buyers. Several reasons have been cited for the AHPs. The issues of the Islamic banking debt based home financing products have remained prominent. The literature argues that these products such as BBA and Tawarruq have embedded features of transferring risks and liabilities to home buyers. This problem becomes acute in cases of AHPs. Musharakah Mutanaqisah or Diminishing Partnership (DP) is suggested as the superior option for Islamic home financing schemes. However, there is hardly any work that has investigated the extent to which DP can provide remedy to address the problem of abandoned housing projects. The present paper adopts content analysis and it shows that DP has a bright prospect of mitigating the problem of abandoned housing projects. The paper is concluded with suggestions for future research.